Representaciones sociales del personal de Recursos Humanos sobre la inclusión laboral de mujeres trans en Santiago de Cali. (2023)
This research arose from the limited and scarce information from studies carried out in Colombia and in the city of Santiago de Cali, about the social representations of Human Resources personnel in the city of Santiago de Cali regarding the labor inclusion of Trans women. . T